Object-oriented Modeling and Simulation of the Arterial Pressure Control System by using MODELICA - Fernández-de-Cañete-Rodríguez, Francisco Javier; Luque, Joaquín; Barbancho, Julio; Muñoz-Martínez, Víctor Fernando (My University, 2013)
The modeling of physiological control systems via mathematical equations reflects the calculation procedure more than the structure of the real system modeled, and several simulation environment have been used so far for this task. Nevertheless, object-oriented modeling is spreading in current simulation environments through the use of the individual components of the model and its interconnections to define the underlying dynamic equations. In this paper we describe the use of the MODELICATM simulation environment in the object-oriented modeling of the cardiovascular control system. The performance of the controlled system has been analyzed by object-oriented simulation in the light of existing hypothesis and physiological data used here for validation purposes.
Keywords: Presión sanguínea - Métodos de simulación; MODELICA; Object oriented modeling; Cardiovascular system; Pressure control